CODE SWITCHING IN JUST ALVIN ON METRO TV - PRIYONO, REZA RESISCA NANDRA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Priyono, Reza Resisca Nandra. 2013. Code Switching in Just Alvin on MetroTV. Study Program of English, Department of Languages and Literature, Facultyof Cultural Studies, Universitas  Brawijaya. Supervisor: Isti Purwaningtyas; Cosupervisor: Istiqomah Wulandari.Keywords: Code Switching, Just AlvinIn the globalization era where worldwide interaction happens, it is quite common for people to use two or more languages as a communication. Indonesiais well known as a multilingual country so that generally Indonesian people havethe ability to speak more than one language. Switching language are commonlydone by people who live in bilingual or multilingual society to avoid misunderstanding among them because of different languages. Here, the study of code switching focuses on conversations found in talk show of TV program. One of TV program which use more than one language and famous nowadays is “Just Alvin” talk show on Metro TV. In this study, the researcher proposed twoproblems of the study, (1) The types of code switching used by Just Alvin’spresenter and the guest stars (2) The viewer’s opinion about the use of codeswitching in the talk show “Just Alvin.This research uses Hoffman’s code switching theory to analyze the data.This study uses qualitative approach in relation to the use of clear and systematic description about the phenomena being studied. Descriptive study in textual analysis is applied in this study to analyze the conversation in “Just Alvin” talk show. The data are selected from 2 videos of “Just Alvin” on Metro TVdownloaded from the internet. The collected data are put into the table and given the analysis of the viewer’s opinion about the used of code switching in the talk show “Just Alvin”.In this research, the researcher found all the types of code switching basedon Hoffman’s theory. The researcher found most of the types of code switching is Intra-sentential code switching.The researcher also found the opinions of the viewers about the use of code switching in the talk show “Just Alvin”. The researcher found according the viewer’s opinions that bilingual languages program give various effects to the viewers. The researcher found most of the opinions are they learn English spoken by the guest star on the talk show, the participants feel interested to bilingual talk show and they enjoy the bilingual talk show.In conclusion, the more the code switching is used, the more it can giveimpact toward the viewer.The researcher suggests the next researchers who want to conduct asimilar research understand more about code switching and also find the reasons why people use code switching. The researcher suggest researchers to apply the latest theories of the types of code switching.